A model for determining the locations of electric vehicles' charging stations in Istanbul - TUZKAYA, GÜLFEM; KILIÇ, HÜSEYİN SELÇUK (PAMUKKALE UNIV, 2019)
The studies about Electric Vehicles (EV) have gained importance and increased in the last years depending on the environmental concerns of the classic transportation systems. One of the problems to consider at this point is locating the proper points of electric charging stations for EVs. The primary objective of this research is to locate the electric charging stations in Istanbul considering the flow of the paths. The locations of electric charging stations are determined by using a mathematical model based on the flow-refuelling location model with the aim of maximizing the captured flow. The mathematical model is run for various values of p and the optimum locations are obtained.
Keywords: Flow-refuelling location model; Assignment problem; Electric vehicles; Electric charging stations; INFRASTRUCTURE; OPTIMIZATION; HYBRID; TRENDS